How Cantillon and Hume Propose the Same Theory of First-Round Effects - Simon Bilo (Duke University, Center for the History of Political Economy (CHOPE), 2015)
Richard Cantillon and David Hume both propose the theory of monetary non-neutrality, whereby the money supply changes through the money balances of specific individuals. Such an uneven distribution of monetary change then spreads throughout the economy step by step and changes relative prices. While a number of authors note that Hume and Cantillon both present the same theory, they do so without seeking confirmation from the original texts. I fill this gap in the literature by identifying the main constituent parts of the theory in the contributions of both Cantillon and Hume.
Keywords: B11; B31; E51; 330; Richard Cantillon; Cantillon effects; first-round effects; David Hume; injection effects